2007
DOI: 10.1063/1.2430027
|View full text |Cite
|
Sign up to set email alerts
|

Laser-scanning angle deviation microscopy

Abstract: A microscope manifesting a dynamic range of several microns and an axial (or height) resolution of 1nm is presented. It is based on the method of angle deviation due to nonfocal plane reflection and the application of surface plasmon resonance effect as well as the technique of heterodyne interferometry. The deviation angle and the induced phase difference between two rays are proportional to the departure from the focal plane. Using the common-path heterodyne interferometry to scan the specimen and measure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…An afocal imaging system (including an objective (8a) and a lens (8b)) magnifies the image after passing through the sample (7). The light is divided into transmission light and reflected light when passing through a beam-splitting prism (9); The transmission light reflects twice in a parallelogram prism (11). The rotation angle near the critical angle is controlled by a controller (Newport: ESP-300, 14) by a combination of a rotation stage (15).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An afocal imaging system (including an objective (8a) and a lens (8b)) magnifies the image after passing through the sample (7). The light is divided into transmission light and reflected light when passing through a beam-splitting prism (9); The transmission light reflects twice in a parallelogram prism (11). The rotation angle near the critical angle is controlled by a controller (Newport: ESP-300, 14) by a combination of a rotation stage (15).…”
Section: Resultsmentioning
confidence: 99%
“…The system could be used for the characterization of internal reflection effect [4] near the critical angle in a prism to measure the reflectivity, thereby leading to the computation of the ray angle and the height of surface. This method differs greatly from traditional ones such as the White-Light Interferometry, the Optical Coherence Tomography (OCT) [5][6][7], Confocal Microscopy [8,9], NSOM: Near-field Scanning Optical Microscopy [10], and Laser-scanning Angle-deviation Microscopy (ADM) [11,12]. Among these reported methods, confocal microscopy [8,9] is best known as an optical scanning microscope.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Schrader et al proposed the 4Pi microscope, whose lateral resolution can be improved into the 100-nm range. 2 Stimulated emission depletion microscopy, which uses two pulsed lasers with a resolution of 30 nm, has been proposed by Hell and Wichmann 3 and Westphal et al 4 In 2007, we reported on using angle deviation microscopy 5 to measure a reflective sample, of which the axial resolution with numerical aperture (NA) = 0.4 is 2.4 nm. In 2008, we reported on transmission-type angle-deviation microscopy (TADM), in which NA = 0.21 (Ref.…”
Section: Introductionmentioning
confidence: 98%
“…Chiu et al proposed a technique for obtaining the surface profile in real time by common-path heterodyne interferometry with a laser to scan the specimen and measure the phase difference distribution. (18) Chen et al designed a compact 2D single-mirror laser scanner. (19) The laser scanner is controlled by three piezoelectric actuators aligned in parallel and has high accuracy.…”
Section: Introductionmentioning
confidence: 99%